2018
DOI: 10.3892/or.2018.6500
|View full text |Cite
|
Sign up to set email alerts
|

HGF derived from cancer‑associated fibroblasts promotes vascularization in gastric cancer via PI3K/AKT and ERK1/2 signaling

Abstract: Cancer‑associated fibroblasts (CAFs) are predominate cells in tumor stroma and play a key role in tumor progression. Hepatocyte growth factor (HGF) is a cytokine mainly derived from fibroblasts. In the present study, we reported that HGF significantly promoted angiogenesis of human umbilical vein endothelial cells (HUVECs) and vasculogenic mimicry (VM) formation of gastric cancer cells, respectively, by increasing cell proliferation and migration. In addition, mosaic vessels formed by HUVECs and gastric cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 44 publications
8
48
0
Order By: Relevance
“…However, the relationship between CAFs and VM formation has rarely been reported. Recently, some studies have con rmed that CAFs can promote VM formation in some tumors, such as HCC [21] and gastric cancer [41,42]. In this study, we observed that GCAFs can promote VM formation and tumor growth of GBCs in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, the relationship between CAFs and VM formation has rarely been reported. Recently, some studies have con rmed that CAFs can promote VM formation in some tumors, such as HCC [21] and gastric cancer [41,42]. In this study, we observed that GCAFs can promote VM formation and tumor growth of GBCs in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 62%
“…At present, the mechanism of CAFs promoting tumor VM formation is not clear. It was reported that CAFs promoted VM formation in HCC by paracrine TGF-β and SDF1 [21]; CAFs-derived HGF promoted vascularization in gastric cancer via PI3K/AKT and ERK1/2 signaling [41]; CAFs induced vasculogenic mimicry in gastric cancer cells through the role of EphA2-PI3K signaling [42]. In order to explore the underlying molecular mechanism of GCAFs promoting VM formation in GBC, in view of aforementioned microarray analysis results, we found that among 154 VM-related genes, NOX4, JAK and STAT3 are involved in VM formation of GBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAFs are important factors in tumor growth and VM formation [73][74][75]. Some studies have demonstrated that TAFs are required for tumor vascularization via various signaling pathways in malignant tumors [76][77][78]. In 2016, Yang et al showed that the conditioned medium of tumor-associated fibroblasts (CM-TAMs) could promote VM formation in vitro through secreting TGF-β and SDF1, and the expression of VE-cadherin, MMP-2, and laminin5γ2 was increased by TGF-β and SDF1 in hepatocellular carcinoma [73].…”
Section: Tumor-associated Fibroblastsmentioning
confidence: 99%
“…It is reported that, in breast cancer, P2RX7 promoted malignant behaviors of cancer cells via activating ERK1/2 and Akt pathways. 13 Considering the ERK1/2 and Akt pathways are crucial modulator of proliferation and apoptosis, 14 we examined that whether P2RX7 had this mechanism by which it promoted gastric cancer progression. As expected, P2RX7 knockdown inhibited the phosphorylated levels of ERK1/2 and Akt, while P2RX7 overexpression activated the phosphorylation of them (Figure 4(a) and (b)).…”
Section: P2rx7 May Increase the Proliferation Of Gastric Cancer Cellsmentioning
confidence: 99%